2004
DOI: 10.1002/er.983
|View full text |Cite
|
Sign up to set email alerts
|

An experimental analysis of a thermodynamic model of a vapour compression refrigeration plant on varying the compressor speed

Abstract: The principal aim of this paper is the study of a thermodynamic model that simulates the working of a vapour compression refrigeration plant. The model allows the evaluation of plant performances when the compressor capacity is regulated varying its velocity by means of an inverter inserted into the compressor electric motor feeder. This type of control allows to match continuously the compressor refrigeration capacity to the load, determining an energy saving in comparison with the classical thermostatic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Additionally, Aprea and Renno [9] have used semi-hermetic compressor in their variable-speed experimental refrigeration cycle and found that the irreversibility rates were 37% at the compressor, 27% at the condenser, 23% at the evaporator and 13% at the expansion valve using R407c as the working fluid. Figure 5 shows the graphical representations of the exergy balance (Grassmann diagram) for the refrigeration system at different frequencies.…”
Section: Resultsmentioning
confidence: 98%
“…Additionally, Aprea and Renno [9] have used semi-hermetic compressor in their variable-speed experimental refrigeration cycle and found that the irreversibility rates were 37% at the compressor, 27% at the condenser, 23% at the evaporator and 13% at the expansion valve using R407c as the working fluid. Figure 5 shows the graphical representations of the exergy balance (Grassmann diagram) for the refrigeration system at different frequencies.…”
Section: Resultsmentioning
confidence: 98%
“…Aprea and Renno [40] investigated the performance of variable speed vapour compression refrigeration system Developments in new refrigerant mixtures M. Mohanraj, C. Muraleedharan and S. Jayaraj working with R407C used for cold storage applications. Their results concluded that exergy loss in the components of the system increases with increase in compressor speed.…”
Section: Domestic Refrigerationmentioning
confidence: 99%
“…Joudi et al [33] investigated the performance of an automobile air-conditioning system working with R12 and HC mixture (composed of R290 and R600a, in the ratio of 62:38, by mole percentage). They performed the experiments at three different ambient temperatures (35,40 and 501C) with six speeds 700, 1000, 1500, 2000, 2500 and 3000 rpm. During their experiments the evaporator chamber was maintained at 45, 50, 55, 60 and 651C.…”
Section: Commercial Refrigerationmentioning
confidence: 99%
“…Variable speed control is another approach to decreasing compressor power because the motor efficiency can be improved at lower speeds when the chiller compressor is operating under a partial load [22,23]. When a variable speed control is applied to the condenser fans, each fan can be operated at a lower speed with a large reduction in power while the condensing temperature remains at its set point.…”
Section: Introductionmentioning
confidence: 99%